2014
DOI: 10.1186/1471-2350-15-83
|View full text |Cite
|
Sign up to set email alerts
|

Association between genetic polymorphisms of cytochrome P450 2C19 and the risk of cerebral ischemic stroke in Chinese

Abstract: BackgroundCytochrome P450 (CYP) 2C19 is a very important drug metabolizing enzyme. Although the single nucleotide polymorphisms (SNPs) of CYP2C19 G681A and G636A have been suggested that they may increase the incidence of cardiovascular events, the relationship between SNPs in CYP2C19 and cerebral ischemic stroke (CIS) are unclear. The aim of this study was to investigate the correlation between the distribution of G681A and G636A polymorphisms in CYP2C19 gene and the risk of CIS in Chinese.MethodsThe peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…Further support is provided by compelling evidence that CYP activity is associated with enhanced local formation of ROS and lipid peroxidation products, which may alter redox signaling pathways and cause oxidative stress-mediated vascular dysfunctions [37] , [38] , [71] , [96] , [97] , [107] . Importantly, they are also consistent with previous studies reporting the association of CYP genetic polymorphisms with different degrees of susceptibility to various cerebrovascular diseases [44] , [46] . In turn, this may reflect the highly polymorphic nature and significant inter-individual and inter-tissue variability in the expression and activity of CYP enzymes, and the consequent variability in the occurrence of local oxidative stress events [39] , [48] , [108] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Further support is provided by compelling evidence that CYP activity is associated with enhanced local formation of ROS and lipid peroxidation products, which may alter redox signaling pathways and cause oxidative stress-mediated vascular dysfunctions [37] , [38] , [71] , [96] , [97] , [107] . Importantly, they are also consistent with previous studies reporting the association of CYP genetic polymorphisms with different degrees of susceptibility to various cerebrovascular diseases [44] , [46] . In turn, this may reflect the highly polymorphic nature and significant inter-individual and inter-tissue variability in the expression and activity of CYP enzymes, and the consequent variability in the occurrence of local oxidative stress events [39] , [48] , [108] .…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, it has been demonstrated that variations in the expression and activity of CYPs can influence the local regulation of cerebral blood flow and vascular homeostasis, and contribute to cerebrovascular diseases [44] , [45] . Consistently, genetic polymorphisms in several CYPs have been associated with inter-individual differences in susceptibility to various vascular and neurological disorders [39] , [46] , [47] , [48] .…”
Section: Introductionmentioning
confidence: 83%
“…The CYP2C19*2 polymorphism was detected by PCR–RFLP analysis, and the platelet function was assessed using conventional aggregometry. A great many of previous studies focused on the relationship between CYP2C19 polymorphism and clopidogrel therapy – related diseases also adopted these technologies, and reported comparable results 31, 32. These might support the validity of our detection on the CYP2C19*2 polymorphism and the platelet function.…”
Section: Discussionsupporting
confidence: 77%
“…In particular, CYP2C19 *2 and *3 (LOF) alleles are associated with a reduced response to standard doses [ 13 , 30 , 31 ]. Notably, a recent study of a Chinese population suggests that CYP2C19 *2 alleles are related to the occurrence and recurrence of cerebral ischaemic stroke [ 32 ]. The major finding of our study is that the combination of three polymorphisms ( CYP2C19 LOF and GOF alleles and ABCB1 C3435T allele) can identify patients at increased risk of developing not only thrombotic events but also major bleeding.…”
Section: Discussionmentioning
confidence: 99%